2012
DOI: 10.1158/1055-9965.epi-12-0717-t
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Plasma Pyridoxal 5′-Phosphate (Vitamin B6) Levels and Invasive Breast Carcinoma Risk: The Multiethnic Cohort

Abstract: Background Evidence from experimental and epidemiological studies suggests that vitamin B6 may reduce the risk of breast cancer. Methods We examined the association of prediagnostic plasma concentrations of pyridoxal-5’-phosphate (PLP), an active form of vitamin B6, with postmenopausal breast cancer risk in a case-control study nested in the Multiethnic Cohort in Hawaii and Southern California, including 706 cases and 706 controls matched on date of birth, ethnicity, study site, date of blood draw, time of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Our finding for an inverse association with higher serum PLP levels on HCC development is consistent with recent data from large longitudinal cohort studies that showed statistically significant strong inverse associations between circulating PLP and incidence of lung cancer (28), colorectal cancer (29) and breast cancer (30). The mechanism(s) by which vitamin B 6 protects against development of these cancers, and HCC in particular, is unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Our finding for an inverse association with higher serum PLP levels on HCC development is consistent with recent data from large longitudinal cohort studies that showed statistically significant strong inverse associations between circulating PLP and incidence of lung cancer (28), colorectal cancer (29) and breast cancer (30). The mechanism(s) by which vitamin B 6 protects against development of these cancers, and HCC in particular, is unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Among the five nested case–control studies, two studies in one article (Wu et al , 1999a) only adjusted for age, menopausal status and year of blood donation, and a positive but not significant association of serum PLP levels with the risk of breast cancer was found. Three studies (Zhang et al , 2003; Lin et al , 2008; Lurie et al , 2012) adjusted for the most known risk factors of breast cancer, and a significantly combined effect (Zhang et al , 2003; Lin et al , 2008; Lurie et al , 2012) was found (0.76 (0.62–0.94), P =0.01, I 2 =0.00%).…”
Section: Resultsmentioning
confidence: 93%
“…Three studies that did not report the risk estimate were also excluded (Potera et al , 1977; Goodman et al , 2001; Schroecksnadel et al , 2003). Finally, 23 articles (Thorand et al , 1998; Wu et al , 1999a; Levi et al , 2001; Shrubsole et al , 2001; Feigelson et al , 2003; Zhang et al , 2003; Zhu et al , 2003; Lajous et al , 2006a; Lajous et al , 2006b; Cho et al , 2007; Kabat et al , 2008; Lin et al , 2008; Xu et al , 2008; Ma et al , 2009a; Ma et al , 2009b; Maruti et al , 2009a; Stevens et al , 2010; Chou et al , 2011; Shrubsole et al , 2011; Zhang et al , 2011; Lurie et al , 2012; Bassett et al , 2013; Yang et al , 2013) were included in this meta-analysis. The detailed steps of our literature search are shown in Supplementary Material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, the square of maximum at 420 nm gradually decreases for 3 rd BC stage. The low level of vitamin B6 in blood was detected in many investigations for patients with advanced BC [20,21]. Peak at 335 nm is defined by tryptophan and tyrosine-containing peptides [18].…”
Section: The Results and Their Discussionmentioning
confidence: 99%